Researching China's policy towards the sectarian conflict in Syria and its future - Linging, Lao (Journal of Humanities & Social Sciences, 2025)
This research analyzes Chinese foreign policy toward current developments in Syria within a theoretical framework derived from international relations theories, with a focus on political realism, constructivism, and role theory. The research relies on a case study methodology supported by comparative analysis, political discourse analysis, and available quantitative data. The findings indicate that China used its veto power in the Security Council on the Syrian issue 16 times between 2011 and 2024, reflecting its commitment to supporting the Syrian regime and preventing unwanted foreign interference. The data also showed that bilateral trade between China and Syria remained limited during the war years (averaging less than $500 million annually), but China has made plans to increase its investments in infrastructure and reconstruction projects if the security situation stabilizes. Critically, it is clear that China has adopted a cautious and pragmatic policy that blends the principles of non-interference with its economic and security interests. However, it has faced a contradiction between its rhetoric supporting inter-Syrian solutions and its practices, which practically serve to strengthen the existing regime. The study concludes that China's success in Syria depends on its ability to strike a better balance between stated principles and actual engagement in reconstruction.
Keywords: China; Syria; foreign policy; sectarian conflict; international relation